Girl-boy differences in perceptions of health determinants and cancer: a more systemic view of girls as young as 6 years - Chloé Gay; Maéliane Deyra; Pauline Berland; Laurent Gerbaud; Frank Pizon (Frontiers Media S.A., 2023)
IntroductionTo model and analyze the differences between girls' and boys' conceptions of the determinants of health and cancer, as expressed and perceived by children and adolescents.MethodA multicentric qualitative study was conducted in five schools (ages 6-11 years), four middle schools (ages 11-15 years), and three high schools (ages 15-18 years). A multi-phase protocol (phase 1 uses the e.Photoexpression© and phase 2 uses the Photonarration) enables children and teenagers to express themselves through photography and storytelling.ResultsA total of 4,174 qualitative productions were produced by 1,068 children, of which 47% were girls and 53% were boys, all in the ages of 6-18 years. From the results of the productions, it can be noticed that children mentioned and were aware of 30 determinants of health and cancer. The three determinants most mentioned were "Consumption of psychotropic drugs", "Diet", and "Harmful environment". Among these 30 determinants, some were mentioned to a greater or lesser extent by girls and boys. These significant gender differences are present for 20 determinants of health and cancer. These differences evolve with age: (1) In elementary school (ages 6-11), girls gave significantly more importance (p < 0.05) to 11 determinants, while boys attached significantly more importance (p < 0.05) to 2 determinants. (2) In middle school (ages 11-16), girls gave significantly (p < 0.05) more importance to 12 determinants, while boys gave significantly (p < 0.05) more importance to one determinant. (3) In high school (ages 15-18 years), girls gave significantly (p < 0.05) more importance to 13 determinants. There was no significant difference (p < 0.05) in favor of boys for high school students. Girls also have a more systemic view of health determinants than boys. The increase in the number of determinants cited by girls is significant (p = 0.017) between the ages of 6-11 and 15-18 years. This gap widens with age (+1.45 determinants) for girls and (+0.68 determinants) for boys between elementary school and high school.ConclusionThe determinants identified as predominantly female or male, as well as age-related specificities, constitute a resource for effective preventive action, as close as possible to the needs and particularities of a population. This mapping of people's conceptions could provide a decision-making aid in defining the strategic orientations of prevention policies.